Arquitetura brutalista como lugar ameno em Teresina: adequação ambiental das obras institucionais de Acácio Gil Borsoi (1970-80) - Andrade, Giesse Monteiro Alves de (2019)
This dissertation deals with the interpretation of the design project of Piauí's Brutalist institutional architecture in the 1970’s and 80’s under the view of the adaptation to the environmental reality of the region. The performance of the Carioca architect Acácio Gil Borsoi as protagonist in the production of different samples of the modern architecture of Piauí, accentuated by the use of vernacular materials and techniques applied to the environmental comfort of the buildings. The dissertation consists of three parts; in the first section, contemplations of a historical nature about modern architecture are made plus the insertion in the context of modern Piauí. At that time, the capital of Piauí underwent a process of modernization through the governmental speech developmentalist, when several institutional buildings were built with the intention of updating the Teresina’s urban landscape in order to adapt it to the socioeconomic moment by which the country passed. The second section deals with the multifaceted trajectory of the architect and the Brutalist works in question. For this purpose, were carried out historiographically based and critical approach. The following is a brief review of regionalism and regional architecture debates, as well as a succinct review of concepts and definitions necessary to elucidate the analysis to be performed. In the third part are described the criteria of qualitative analysis of the works under study, based on the bibliography of Armando de Holanda, contemporary architect and disciple of Borsoi. The selection of Borsoi’s two buildings- the Court of Justice (1972) and the Legislative Assembly of the State of Piauí (1984), located in the Civic Center – also help to understand the relationship between modern architecture and regionalization constructive as result climate result. Such examples are loaded with a relationship between the architect's design concept and the bioclimatic factors of the region. Thus, they add regional characteristics to the modern Piauí architecture, wich makes it unique.